2017
DOI: 10.1016/j.ensci.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of migraine among students in Mali

Abstract: Migraine is a debilitating but benign disease that can affect the quality of life of patients, disrupt the emotional relationships and impact on educational and vocational activities. The aim of our work was to study the epidemiology and impact of migraine in schools in the urban district of GAO in Mali.This is a cross-sectional study among students in the city of Gao. The survey was conducted in 11 schools, each of which represented a cluster. The study involved 733 students and diagnosis of migraine was made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
(23 reference statements)
1
6
0
Order By: Relevance
“…Studies of student populations have found a prevalence of 11.3% in Cotonou and 14.2% in Parakou in Benin and 17.3% in Mali [20,38,39]. In our study, it was 11%, with 31 students and / or students, results that are similar to those of the above studies.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Studies of student populations have found a prevalence of 11.3% in Cotonou and 14.2% in Parakou in Benin and 17.3% in Mali [20,38,39]. In our study, it was 11%, with 31 students and / or students, results that are similar to those of the above studies.…”
Section: Discussionsupporting
confidence: 91%
“…Migraine, like other primary headaches, affects all socioprofessional classes [20,23,38]. In our study, migraine affects all occupations but with a predominance for informal sector workers (32.2%) and students / students (31.7%).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Migraine is a common neurological disorder that is characterized by idiopathic and recurrent attacks of headache. 1 Migraine is generally associated with personal burden which is a result of headache related disability, higher rates of co-morbidities, reduced health related quality of life and direct and indirect costs. 2,3 Person living with migraine who are chronically affected have recurrent episodic attacks that may progress to severe and frequent attack patterns.…”
Section: Introductionmentioning
confidence: 99%